2014
DOI: 10.1155/2014/589412
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Circulating and Endothelial Progenitor Cell Markers in Type 2 Diabetic Foot

Abstract: Objective. We studied circulating precursor cells (CPC) in type 2 diabetes mellitus (T2DM) with neuropathic foot lesions with or without critical limb ischemia and relationships between endothelial precursor cells (EPC) and peripheral neuropathy. Methods and Subjects. We measured peripheral blood CD34, CD133, and CD45 markers for CPC and KDR, CD31 markers for EPC by citofluorimetry and systemic neural nociceptor CGRP (calcitonin gene related protein) by ELISA in 8 healthy controls (C) and 62 T2DM patients: 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…[7][8][9][10][11][12] The lower frequency of HSCs in persons with diabetes has been associated with a higher risk of progress and severity of diabetic vascular complications, including DN 8,13,14 and diabetic foot wounds. [15][16][17][18] Different types of HSCs have been used to successfully treat diabetic animal models of DN. [19][20][21][22][23] HSCs can differentiate into hepatocytes, epithelial cells, 24 cardiomyocytes, smooth muscle cells, or endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] The lower frequency of HSCs in persons with diabetes has been associated with a higher risk of progress and severity of diabetic vascular complications, including DN 8,13,14 and diabetic foot wounds. [15][16][17][18] Different types of HSCs have been used to successfully treat diabetic animal models of DN. [19][20][21][22][23] HSCs can differentiate into hepatocytes, epithelial cells, 24 cardiomyocytes, smooth muscle cells, or endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Additional causality and mechanistic studies are needed to more clearly define the relationship between CACs and diabetes in humans. Nevertheless, indications from prior human and animal studies are consistent with the idea that attenuated vascular repair due to low levels of pro-angiogenic cells, or dysfunctional pro-angiogenic cells promotes endothelial dysfunction and pathological outcomes such as retinopathy [ 29 ], neuropathy [ 11 , 35 ], and nephropathy [ 10 , 36 ].…”
Section: Discussionmentioning
confidence: 59%
“…CD34 is a well-described marker for HPCs, predicting enhanced cellular function and improved therapeutic potential [3335]. Immunohistochemistry demonstrated that dHACM stimulated a significant increase in CD34 + progenitor cells in the peri- implant space and surrounding skin compared with both sham surgical sites and healthy skin (4-fold, day 14; 3-fold, day 28; P ≤ 0.05) and control ADM (2-fold, day 14; 3-fold, day 28; P ≤ 0.05) (Fig.…”
Section: Resultsmentioning
confidence: 99%